A ratiometric fluorescence platform composed of MnO2 nanosheets and nitrogen, chlorine co-doped carbon dots and its logic gate performance for glutathione determination. (7th January 2022) - Bai, Fujuan; Wang, Haiwei; Lin, Longyi; Zhao, Longshan
Abstract : Illustration of the principle of a dual-emission ratiometric fluorescence strategy for the selective detection of GSH based on an N, Cl-CD-assisted MnO2 nanosheet–OPD system. Abstract : Herein, a ratiometric fluorescence strategy based on MnO2 nanosheets and nitrogen, chlorine co-doped carbon dots (N, Cl-CDs) was constructed for selective determination of glutathione (GSH) and the absolute fluorescence quantum yield of N, Cl-CDs was 14.8%. The MnO2 nanosheets with oxidase-like activity could catalytically oxidize o -phenylenediamine (OPD) to generate the yellow fluorescent 2, 3-diaminophenazine (DAP). Moreover, the fluorescence of N, Cl-CDs was quenched by DAP through the inner filter effect (IFE). The fluorescence signal of DAP decreased at 565 nm, whereas that of N, Cl-CDs increased at 440 nm (at an excitation wavelength of 380 nm) because GSH decomposed the MnO2 nanosheets into Mn 2+ . The fluorescence intensity ratio of F 440 / F 565 increased linearly in the range of 10–500 μM GSH and the limit of detection was 3 μM for GSH. The actual application of the established method in human serum samples was evaluated and verified by standard experiments, and the recoveries of spiked samples ranged from 96.6% to 108.1% with a relative standard deviation (RSD) less than 2.0% ( n = 3). Moreover, a logic gate device was investigated by setting MnO2 nanosheets and GSH as two input signals and the emission of N, Cl-CDs and DAP as two outputs, implying that the sensing platform has potential application in the field of intelligent GSH detection systems.